Spatial Analysis of Residents’ Response to Fear of Crime in Osogbo, Osun State, Nigeria - Farodoye, Seyi Oloyede; Olawuni, Peter O.; Oladehinde , Gbenga John; Atoyebi, Olumuyiwa Sola; Ayoola, Lukuman Opeyemi (Richtmann Publishing, 2021)
The study investigated spatial pattern of residents' response to the fear of crime in Osogbo Local Government Area, Osun State, Nigeria. Primary data was collected by stratifying the Osogbo into three residential neighborhoods, namely; core, transition, and suburban areas. Systematic sampling was used in selecting 112 respondents across residential neighborhoods. The level of Crime Occurrence Index (LCOI) in the core area was 5.03 while 5.90 and 5.31 were indices for transition and suburban areas. The study recorded that religion, police patrol, lightning, membership/ support of vigilante and use of joint community responses were the commonly used strategy in responding to fear of crime while insurance scheme, burglary alarm system, closed-circuit television (CCTV), and surveillance camera were the least strategies used in responding to fear of crime in the study area. The study concludes that there is a significant difference in the responses of residents to fear of crime in the various residential neighborhoods. Received: 21 December 2020 / Accepted: 18 February 2021 / Published: 7 March 2021